P508Biventricular pacing versus His bundle pacing after atrioventricular node ablation in heart failure patients with permanent atrial fibrillation and narrow QRS. (18th June 2020) - Zizek, D; Antolic, B; Zavrl-Dzananovic, D; Klemen, L; Jan, M; Zupan Meznar, A; Breskvar Kac, U D; Stublar, J; Zupan, I; Sinkovec, M
Abstract: Background: Atrioventricular (AV) node ablation with biventricular (BiV) pacemaker implantation is a feasible rate control strategy for symptomatic permanent atrial fibrillation (AF) with rapid ventricular response and tachycardia-induced heart failure (HF). However, certain controversy exists since BiV pacing delivers non-physiological ventricular resynchronization and does not return left ventricular (LV) activation times to those seen in individuals with intrinsically narrow QRS. Permanent His bundle pacing (HBP) is a physiological alternative to conventional and BiV pacing. By capturing the native conduction system, depolarization of the ventricles through the His-Purkinje system induces normal synchronous ventricular activation. Purpose: The aim of the study was to compare short-term outcomes between BiV pacing and HBP after AV node ablation in HF patients with symptomatic permanent AF and narrow QRS. Methods: A total of 25 consecutive HF patients with permanent AF and narrow QRS (≤110 ms) who underwent AV node ablation in conjunction with BiV pacing or HBP in our centre were enrolled. Post-implant QRS duration, echocardiographic data, and New York Heart Association (NYHA) functional class were assessed in short-term follow-up. Results: Among 25 HF patients (aged 68 ± 7 years, 52% female, QRS 96 ± 9 ms, LVEF 37 ± 7%, NYHA II-IV), 13 received BiV pacing and 12 HBP. Implant and ablation procedures were acutely successful in both groups. In BiV group 1 patient had a LV lead dislodgement and 1 patient in the HBP group had an acute HB lead threshold increase after AV node ablation. In HBP group post-implant QRS duration was shorter compared to BiV (103 ± 15 ms vs. 177 ± 13 ms, p < 0.001). At a median follow-up of 6 months, patients treated with HBP had greater increase in LV ejection fraction compared to BiV (44 ± 10 vs. 37 ± 6, p = 0.045). A trend toward greater reduction of LV volumes (EDV 119 ± 54 ml vs. 153 ± 33 ml, p = 0.07; ESV 75 ± 34 ml vs. 97 ± 26 ml, p = 0.09) and improvement of NYHA class (2.1 ± 0.7 vs. 2.7 ± 0.8, p = 0.08) was also observed in HBP group compared to BiV group. Conclusion: In rate control refractory HF patients with permanent AF and narrow QRS atrioventricular node ablation in conjunction with HBP demonstrated superior electrical resynchronization and greater increase in LV ejection fraction compared to BiV pacing. Larger prospective studies are warranted to address clinical outcomes between both pace and ablate strategies.